Relationships between postpartum depression, sleep, and infant feeding in the early postpartum: An exploratory analysis - Rudzik, Alanna E. F.; Robinson-Smith, Lyn; Tugwell, Francesca; Ball, Helen L. (Frontiers in Psychiatry, 2023)
Introduction: The study objectives were to determine the relationships between postpartum depression and maternal and infant sleep parameters and to examine the impact of infant feeding method on infant and maternal sleep and postpartum depression symptomatology. Methods: Participants were 61 new mothers aged 18 to 45 years old, and their full-term, normal birth-weight, singleton infants. Participants were recruited from a large teaching hospital in northeast England. Data collection took place in participants’ homes. The study used a prospective longitudinal design, with data collected at six, 12 and 18 weeks postpartum. We collected data on total sleep time, longest sleep period, wake after sleep onset, and night waking for mothers and infants objectively from actigraphic records and subjectively from maternal sleep logs. Participants reported on sleep disturbances using the General Sleep Disturbances Scale, on maternal sleepiness, and on depression symptomatology using the Edinburgh Postnatal Depression Scale. Results: Scores on the Edinburgh Postnatal Depression Scale and General Sleep Disturbances Scale were consistently correlated with each other (6 weeks r=0.452, p<0.01; 12 weeks r=0.317, p<0.05; 18 weeks r=0.493, p<0.01), and did not correlate with objective measures or subjective reports of maternal or infant sleep. Edinburgh Postnatal Depression Scale scores at six, 12 and 18 weeks were predicted by General Sleep Disturbances Scale, prior Edinburgh Postnatal Depression Scale score, or both, but not by sleep parameters. With regard to infant feeding method, EPDS score was not higher among exclusively breastfeeding than among exclusively formula-feeding participants at any time point (6 weeks t=0.306, p=0.762; 12 weeks t=0.343, p=0.733;18 weeks t=0.426; p=0.673). Different pathways emerged to predict Edinburgh Postnatal Depression Scale score for exclusively breastfeeding and exclusively formula-feeding women. Discussion: Postpartum depression may be associated with disturbed sleep due to negative perception of sleep among depressed women, rather than disrupted sleep causing postpartum depression. With regard to infant feeding method, exclusively breastfeeding women are not more likely to suffer from postpartum depression, and different pathways may predict development of postpartum depression symptoms in exclusively breastfeeding and exclusively formula-feeding women.